The effects of advisory services and technology channeling on farm yields and technical efficiency of wheat farmers in Ethiopia - Yitayew, Asresu; Abdulai, Awudu; Yigezu, Yigezu (Elsevier, 2023)
Improving the performance of low-productivity smallholder farmers is a pathway with great potential for reducing poverty and enhancing food security and nutrition in sub-Saharan Africa. Using experimental data from Ethiopia and a mediated stochastic frontier model that accounts for endogenous treatment status, we examine the impact of advisory services and technology channeling on farm yields and efficiency. Our results show that the impact of improved extension services on yields is positive and statistically significant and that advisory services constitute a significant proportion of the output effect.